Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.jshs.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, fitness, and all-cause mortality: An 18-year follow-up among old people

Abstract: BackgroundLittle is known about change in physical activity (PA) and its relationship to all-cause mortality among old people. There is even less information about the association between PA, fitness, and all-cause mortality among people aged 80 years and above. The objective is to investigate persistence and change in PA over 5 years as a predictor of all-cause mortality, and fitness as a mediator of this association, among people aged 80 and 85 years at the beginning of an 18-year mortality follow-up period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…1,1518,20,21,25,26,31,39,4244 The results of this current study of older Mexican Americans show that increased PA with age results in a 43% reduction of mortality risk compared to unchanged low activity, after controlling for all covariates. The mortality risk from increasing PA was more favorable that an unchanging high level of PA after 3 years.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…1,1518,20,21,25,26,31,39,4244 The results of this current study of older Mexican Americans show that increased PA with age results in a 43% reduction of mortality risk compared to unchanged low activity, after controlling for all covariates. The mortality risk from increasing PA was more favorable that an unchanging high level of PA after 3 years.…”
Section: Resultsmentioning
confidence: 53%
“…Investigators have found that an increase in PA or maintenance of a high PA level results in a more favorable mortality outcome compared to unchanged low levels of PA. 1217 Furthermore, maintaining a low level of PA or decreasing PA over time increases the risk for premature death. 1214,18 However, few studies that evaluate the effect of changing PA level differentiate between PA domains or investigate this relationship among Mexican-Americans who have a lower mortality rate and a higher rate of non-leisure time PA. 10,11 There is some evidence that suggests sustained PA and consistent non-sedentariness improve mortality rates among Hispanics, 16,19 but these studies are not specific to Mexican-Americans 19 and were exclusively among myocardial infarction patients. 16 PA domains, such as leisure-time, walking and household activities, have been shown to reduce mortality risk among older Mexican Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Differences between groups (based on choice of programme) for baseline characteristics were analysed using Chi-square test (Fisher's exact test if expected count were <5), Student's t-test or Mann-Whitney U-test depending on variable. The activity level of the SGPALS was dichotomized into groups of being inactive (level 1-2) or active (level 3-6) using the same method as Äijö et al [27].…”
Section: Discussionmentioning
confidence: 99%
“…We found that total physical activity was associated with fitness level regardless of domain, which was consistent with previous studies and existing guidelines. [33][34][35][36] ACSM/AHA recommend adults aged 18-65 need 30 minutes moderateintensity physical activity on five days each week or 20 minutes vigorous-intensity physical activity on three days each week which can be accumulated from bouts lasting 10 or more minutes. As long as the accumulation of short bout physical activities reached the minimum amount of total activity per week, total physical activity of all domains could give benefit to fitness level.…”
Section: Discussionmentioning
confidence: 99%